Export diversification and economic growth: A threshold regression approach for emerging markets and developing countries - Pham Thi Tuyet Trinh; Hoang Thi Thanh Thuy (Economic Journal of Emerging Markets, 2021)
Purpose - This study investigates the nonlinear relationship between export diversification and economic growth in 44 emerging markets and developing countries.Methods - The threshold regression methodology is employed to analyze data for the period between 1995 and 2015. Export diversifications in terms of both geography and product are measured by the Herfindahl-Hirschman market concentration index and overall Theil index, respectively.Findings - The results demonstrate a nonlinear relationship between export diversification and economic growth. Above the threshold, diversified export markets and products boost economic growth. Below the threshold, the positive relationship between diversification in both markets and products and growth is insignificant.Implications - The research implies that export diversification strategy in emerging markets and developing countries should be considered carefully when the level of export diversification is higher than the threshold, which usually occurs in the later stage of diversification.Originality - The study investigates nonlinearity in terms of degrees of diversification instead of degrees of development. With this approach, the threshold is identified to show how economic growth is affected under different regimes.